The feasibility of organ transplantation during the COVID-19 outbreak: experiences from South Korea - Juhan Lee; Eun Jin Kim; Kyong Ihn; Jae Geun Lee; Dong Jin Joo; Myoung Soo Kim; Soon Il Kim; Yu Seun Kim; Kyu Ha Huh (Korean Journal of Transplantation, 2020)
Background : The coronavirus disease 2019 (COVID-19) has forced healthcare systems to reduce transplant activities in order to preserve resources and minimize the risk of nosocomial transmission. Although transplantation societies around the world have proposed interim recommendations, little is known about the safety of transplant surgery under pandemic conditions and how transplant medicine should move forward after the peak of the pandemic. Methods : We describe our experiences regarding the continuation of living and deceased donor transplantation under infection control measures during the COVID-19 outbreak in South Korea. We reviewed consecutive liver and kidney transplantations at Severance Hospital and analyzed national transplantation activities in South Korea. Results : Transplantation activities with living and deceased donors remained stable during the COVID-19 outbreak compared to the same period in 2019. We performed 94 transplantations (58 kidney, 35 liver, and 1 simultaneous liver-kidney) during the COVID-19 outbreak. Twenty-five patients underwent desensitization therapy prior to transplant (nine ABO-incompatible kidney, eight human leukocyte antigen-incompatible kidney, and eight ABO-incompatible liver). No transplant recipients in our center contracted COVID-19. In South Korea, national transplant activities with living and deceased donors remained stable in 2020 compared to 2019. Conclusions: Organ transplantation during pandemics appears to be feasible with appropriate infection prevention measures.